2002
DOI: 10.1177/0170840602233001
|View full text |Cite
|
Sign up to set email alerts
|

Governmentality Matters: Designing an Alliance Culture of Inter-Organizational Collaboration for Managing Projects

Abstract: Go ov ve er rn nm me en nt ta al li it ty y M Ma at tt te er rs s: : D De es si ig gn ni in ng g a an n A Al ll li ia an nc ce e C Cu ul lt tu ur re e o of f I In nt te er r-O Or rg ga an ni iz za at ti io on na al l C Co ol ll la ab bo or ra at ti io on n f fo or r M Ma an na ag gi in ng g P Pr ro oj je ec ct ts s

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
208
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(213 citation statements)
references
References 29 publications
3
208
0
2
Order By: Relevance
“…She suggests that employees who feel precarious are more likely to feel the need to internalize this discourse in order to appear favorable to superiors. Similar results have been noted in relation to the way management accounting systems (Ezzamel and Willmott, 1998), project management (Hodgson, 2002;Clegg et al 2002), diversity (Zanoni and Janssens ( 2004), strategy (Knights and Morgan, 1991;Laine and Vaara, 2007) and billable hours (Brown and Lewis, 2010) can exert a discursive pressures that subjectify subordinates in this manner.…”
Section: Subjectification 'In' Organizationssupporting
confidence: 60%
“…She suggests that employees who feel precarious are more likely to feel the need to internalize this discourse in order to appear favorable to superiors. Similar results have been noted in relation to the way management accounting systems (Ezzamel and Willmott, 1998), project management (Hodgson, 2002;Clegg et al 2002), diversity (Zanoni and Janssens ( 2004), strategy (Knights and Morgan, 1991;Laine and Vaara, 2007) and billable hours (Brown and Lewis, 2010) can exert a discursive pressures that subjectify subordinates in this manner.…”
Section: Subjectification 'In' Organizationssupporting
confidence: 60%
“…Power also may be less explicitly articulated through the role of surveillance (Lukes, 2005;Clegg et al, 2002). The breakdown of relationships and the build-up of distrust is indentified in the cases, often in relation to competition.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is strong evidence from 'traditional' private sector organizations that the achievement of a practical collective consciousness has been seen as problematic; it is even more so under newer forms of organizational design where there is no unitary centre of control (Clegg et al 2002). Weitzenboeck (2001) reported that in one commercial sector, the maritime industry, participants in virtual organizations initially saw their working relationship in terms of trust and shared purpose; however, in practice they faced difficulty building trust and recognised a need for legal frameworks to regulate their activities.…”
Section: Children's' Trusts: a Public Sector Virtual Organization?mentioning
confidence: 99%